2002
DOI: 10.1089/109264202762252695
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Laparoscopic Ventral Hernia Repair in Correlation with Obesity, Type of Hernia, and Hernia Size

Abstract: Laparoscopic repair of incisional and larger hernias is a technically demanding procedure that requires a longer operative time. In contrast to PVH repair, laparoscopic IVH repair usually cannot be performed on an outpatient basis. Surgeons need not be discouraged from recommending the laparoscopic approach for patients with large IVHs or with severe obesity because the morbidity remains low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 8 publications
3
37
0
Order By: Relevance
“…Bower et al 53 reported a 4% recurrence in a short-term follow-up of 47 obese and morbidly obese patients. One recurrence was also observed in the small series by Raftopoulos et al 30 after removal of an infected mesh. Unfortunately, the length of follow-up was not reported by that group of investigators.…”
Section: Commentsupporting
confidence: 51%
“…Bower et al 53 reported a 4% recurrence in a short-term follow-up of 47 obese and morbidly obese patients. One recurrence was also observed in the small series by Raftopoulos et al 30 after removal of an infected mesh. Unfortunately, the length of follow-up was not reported by that group of investigators.…”
Section: Commentsupporting
confidence: 51%
“…There are recent publications that report the favorable outcome of laparoscopic ventral hernia repair in obese patients [2,10], A MEDLINE search, however, returned no articles that specifically addressed the management of ventral hernias in patients undergoing LGB.…”
mentioning
confidence: 99%
“…Morbid obesity is not a contraindication to laparoscopic repair and represents an advantage both for the patient and the surgeon. 26 The recurrence rate in this study was 4.41% in the open group compared to nil in the laparoscopic group. All the patients could not be followed up due to lack of patient's interest.…”
Section: Discussionmentioning
confidence: 47%